Differential Lipid Composition and Gene Expression in the Semi-Russeted “Cox Orange Pippin” Apple Variety - Legay, Sylvain; Cocco, Emmanuelle; André, Christelle M.; Guignard, Cédric; Hausman, Jean-Francois; Guerriero, Gea (Frontiers in Plant Science, 2017)
Russeting is characterized by a particular rough and brown phenotype, which is mainly due to the accumulation of suberin in the inner part of the epidermal cell walls. In our previous bulk transcriptomic analysis, comparing fully russeted and waxy apple varieties, showed, in apple fruit skin, a massive decreased expression of cutin, wax and some pentacyclic triterpene biosynthesis genes in the russeted varieties, with an expected concomitant enhanced expression of the suberin biosynthetic genes. In the present work, we performed a deep investigation of the aliphatic composition of the cutin, suberin, waxes and triterpenes in the waxy and russeted patches of the semi-russeted apple variety ‘Cox Orange Pippin’. A targeted gene expression profiling was performed to validate candidate genes which were identified in our previous work and might be involved in the respective metabolic pathways. Our results showed that a decrease of cuticular waxes, ursolic acid and oleanolic acid, accompanied by an accumulation of alkyl-hydroxycinamates and betulinic acid, occurs in the russeted patches. The suberin monomer composition is characterized by specific contents in 20, 22 and 24 carbon aliphatic chains, whereas cutin is mainly represented by common C16 and C18 aliphatic chains. This work depicts, for the first time in apple, the complex composition of suberin, cutin, waxes and triterpenes, and confirms the strong interplay between these epidermal polymers in apple fruit skin.